REFORMS IN THE CULTURAL FIELD - AS THE BASIS OF A NEW SPIRITUAL SPACE - Mamatkulov Eldor Safarovich (American Journals Publishing, 2024)
This article presents opinions on the interrelationship of culture and spirituality, the importance of cultural reforms in creating a new spiritual environment. The main aspects of the reforms implemented in our country regarding the creation of a new spiritual space have been analyzed.
Keywords: Culture, spirituality, cultural reforms, dialectics, spiritual culture, the third renaissance.